Acting Proactively to Manage Job Insecurity: How Worrying About the Future of One’s Job May Obstruct Future-Focused Thinking and Behavior - Koen, Jessie; van Bezouw, Maarten J. (Frontiers in Psychology, 2021)
An increasing number of people experience insecurity about the future of their job, making it more important than ever to manage this insecurity. While previous research suggests that proactive coping is a promising way to alleviate job insecurity, we suggest that, paradoxically, it may be particularly difficult to act proactively when feeling emotionally distressed about the future of one’s job. Drawing on the principle of resource scarcity and the Conservation of Resources theory, we propose that affective job insecurity ignites a scarcity mindset that inhibits workers’ future focus and cognitive functioning, thereby undermining proactive career behavior. Additionally, we examine whether income adequacy can compensate for these negative consequences of job insecurity. Results of a three-wave survey study among 108 self-employed professionals during the COVID-19 pandemic showed that initial affective job insecurity was negatively related to cognitive functioning but unrelated to future focus. Yet, the latter relationship was moderated by income adequacy: affective job insecurity was positively related to future focus when participants reported high income adequacy. In turn, future focus was positively related to proactive career behavior, which was subsequently related to lower cognitive job insecurity. Thus, while replicating the finding that workers can proactively manage their cognitive job insecurity, we also showed that initial affective job insecurity may obstruct people’s cognitive functioning. We discuss how our results signal a Matthew effect, in which job insecure people with sufficient means are able to look ahead and proactively build resources to change their career, while job insecure people with insufficient means may fall behind.